Ownership structure, firm age, and technological capital as determinants of firm performance and value - Zulfikar Ikhsan Pane; Yustina Triyani; Ingkak Chintya Wangsih (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2025)
This study examines the effects of ownership structure, firm age, and technological capital on firm performance and firm value. Using a final sample of 99 observations from manufacturing sector companies in Indonesia over the period 2020–2022, the findings reveal that only firm age and technological capital have a positive and statistically significant effect on firm performance. Further analysis indicates only technological capital has a positive and significant effect on firm value. These results suggest that the longer a firm operates, the greater its production scale and cost-efficiency capabilities become; however, such maturity alone is insufficient to convince investors. In contrast, a firm’s ability to adapt to and develop technological capabilities not only enhances profitability but also increases its stock price in capital market.